2020
DOI: 10.1042/bsr20194337
|View full text |Cite
|
Sign up to set email alerts
|

Mining TCGA database for tumor mutation burden and their clinical significance in bladder cancer

Abstract: Background: Bladder cancer is the ninth most-common cancer worldwide and it is associated with high morbidity and mortality. Tumor mutational burden (TMB) is an emerging biomarker in cancer characterized by microsatellite instability. TMB has been described as a powerful predictor of tumor behavior and response to immunotherapy. Methods: A total of 443 bladder cancer samples obtained from The Cancer Genome Atlas (TCGA) were analyzed for mutation types, TMB values, and prognostic value of TMB. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 50 publications
4
79
0
Order By: Relevance
“…KLF15 has been reported to inhibit cell growth in lung adenocarcinoma (37), gastric cancer (38), and colorectal cancer (39), and can be used to predict prognosis. High ADRA2A expression was associated with poor overall survival for breast (40) and bladder cancer (41). As a genetic marker, RNASEL has been linked to lethal prostate cancer (42).…”
Section: Discussionmentioning
confidence: 99%
“…KLF15 has been reported to inhibit cell growth in lung adenocarcinoma (37), gastric cancer (38), and colorectal cancer (39), and can be used to predict prognosis. High ADRA2A expression was associated with poor overall survival for breast (40) and bladder cancer (41). As a genetic marker, RNASEL has been linked to lethal prostate cancer (42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TMB was independent of the expression of PD-L1, which was the strongest feature associated with a therapeutic effect in multivariate analysis (37). Lv et al (2020) revealed that the prognosis of bladder cancer patients with higher TMB was better so that TMB was considered to be a powerful predictor of tumor behavior and response to immunotherapy (38). However, in some types of cancer, such as clear cell renal cell carcinoma, patients with high TMB levels showed worse survival outcomes (24).…”
Section: Discussionmentioning
confidence: 99%
“…The ‘maftools’ software package was utilized to analyze and visualize the immune cell biomarker-associated mutation data [ 103 ]. The immune cell biomarker-associated mutation data were compared between one group and the other groups using the chi-square test.…”
Section: Methodsmentioning
confidence: 99%